Vitamin K Deficiency Embryopathy from Hyperemesis Gravidarum - Andrew S. Lane; Jennifer L. Stallworth; Kacey Y. Eichelberger; Kenneth F. Trofatter (Case Reports in Obstetrics and Gynecology)
A 21-year-old primigravida had a pregnancy complicated by hyperemesis gravidarum (HG) beginning at 7-week gestation. Despite medical therapy, she lost 18% of her prepregnancy weight. Early ultrasound at 14 weeks demonstrated a flattened facial profile with nasal hypoplasia (Binder phenotype) consistent with vitamin K deficiency from HG. She had a percutaneous endoscopic gastrojejunostomy tube placed for enteral feeding at 15-week gestation. At repeated anatomy ultrasound at 21-week gestation, delivery, and postnatal pediatric genetics exam, nasal hypoplasia was consistent with vitamin K deficiency embryopathy from HG. Nausea and vomiting of pregnancy is a common condition. HG, the most severe form, has many maternal and fetal effects. Evaluation of vitamin K status could potentially prevent this rare and disfiguring embryopathy.